Virtual reality for validation of automatic bone fracture reduction algorithms - Jimenez-Delgado, Juan Jose; Parra-Cabrera, Gema; Perez-Cano, Francisco Daniel; Silva, Augusto (2022 International Conference on Graphics and Interaction (ICGI), 2022)
This paper presents a virtual world for bone fracture reduction. The environment is designed to facilitate interaction and immersion of the specialist in a realistic ambience improving fracture visualization and facilitating fracture reduction. Subsequently, the reduction data is collected and compared with the data provided by the automatic reduction algorithms. It is intended to provide an environment for the validation of the reductions where the expert establishes the optimal reduction. The system has been tested by specialists in the field of traumatology and computer science familiar with the subject of study and is an improvement on a first version in which the degree of realism of the interaction was lower.